Simile as an Indispensable Element of Expressiveness - Dalalyan, Manana; Mkrtchyan, Hasmik (Armenian Folia Anglistika, 2015)
Every piece of fiction is a piece of poetic accessory. Poetic language is conditioned by the unification of incompatible notions, implicitness and covertness to make the language of fiction attractive. The means of language spicing may vary. The variety of means may depend on different factors such as gender, age, linguo-cultural identity, national characteristics, special preference of tropes and figures of speech, which may lead to the identification of the individual style of the author. Text is a unity of reality, concepts and meanings which are to be essentially decoded by the reader. Every writer explores the world differently, touches different problems from different angles and definitely has a special preference to a set of particular stylistic means to express himself/herself. The means making the author’s works mostly recognizable can be a set of simile, metaphor, hyperbole, personification, stylistic inversions, etc.